Novinarstvo in internet - Erjavec, Karmen (Teorija in praksa, 2012)
The authors analyse the personality characteristics of hate speech writers in comments under web news items. Through in-depth interviews they try to identify their values and beliefs as well as their type of personality. The first group of writers consists of "soldiers" who are organised, while the second one includes "believers", "players" and "watchdogs" who act on their own initiative. The main motive of the soldiers and believers is completing the mission; they share characteristics of an authoritarian personality. The players are motivated by thrill and fun, and the watchdogs by drawing attention to social injustices; these two subgroups have the characteristics of a libertarian personality
Keywords: Hate speech; Sovražni govor; Journalism; Novinarstvo; Commentary; Komentar; Spletno novinarstvo; Online journalism; Readers; Internet; Bralci; Slovenia; Slovenija